Optimal antimicrobial concentration of mixed antibiotic pastes in eliminating Enterococcus faecalis from root dentin - Anat Dewi (2020)
© 2020 Australian Society of Endodontology Inc This study aims to identify the optimal concentrations of triple antibiotic paste (TAP), modified triple antibiotic paste (mTAP) and double antibiotic paste (DAP) that could completely eradicate Enterococcus faecalis in dentinal tubules. One hundred and ninety extracted human premolars inoculated with E. faecalis were medicated with calcium hydroxide and mixed antibiotic pastes (TAP, mTAP and DAP at 0.1, 1.25, 5, 10 and 20 mg mL−1 of each drug) for seven days before being frozen, pulverised and cultured. Specimens treated with the lowest concentration of the mixed antibiotics capable of eradicating E. faecalis were examined using scanning electron and confocal laser scanning microscopy to confirm the eradication of the microbial. TAP at 10 mg mL−1 of each drug was able to completely eliminate bacteria inside dentinal tubules, whereas mTAP and DAP required 20 mg mL−1 of each drug. Calcium hydroxide was not effective in eradicating E. faecalis inside dentinal tubules.